PRC2 specifies ectoderm lineages and maintains pluripotency in primed but not naïve ESCs - Yongli Shan (Nature Portfolio, 2017)
Polycomb repressive complex 2 (PRC2) plays an essential role in development by modifying chromatin but what this means at a cellular level is unclear. Here, the authors show that ablation of PRC2 genes in human embryonic stem cells and in mice results in changes in pluripotency and the primed state of cells.